1999
DOI: 10.1111/1467-8624.00081
|View full text |Cite
|
Sign up to set email alerts
|

All Other Things Being Equal: Acquisition and Transfer of the Control of Variables Strategy

Abstract: The ability to design unconfounded experiments and make valid inferences from their outcomes is an essential skill in scientific reasoning. The present study addressed an important issue in scientific reasoning and cognitive development: how children acquire a domain-general processing strategy (Control of Variables Strategy or CVS) and generalize it across various contexts. Seven-to 10-year-olds ( N ϭ 87) designed and evaluated experiments and made inferences from the experimental outcomes. When provided with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
591
3
39

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 594 publications
(676 citation statements)
references
References 63 publications
43
591
3
39
Order By: Relevance
“…By contrast, the transfer problem formats remained unfamiliar to the children at posttest, so had to be solved by applying or adapting procedures learned during the interventiona standard approach for measuring transfer (e.g., Atkinson et al, 2003;Chen & Klahr, 1999). Children were encouraged to show their calculations when solving the problems.…”
Section: Assessmentsmentioning
confidence: 99%
“…By contrast, the transfer problem formats remained unfamiliar to the children at posttest, so had to be solved by applying or adapting procedures learned during the interventiona standard approach for measuring transfer (e.g., Atkinson et al, 2003;Chen & Klahr, 1999). Children were encouraged to show their calculations when solving the problems.…”
Section: Assessmentsmentioning
confidence: 99%
“…Domain-general knowledge, often referred to as ''process skill,'' includes knowledge that transcends any specific branch of science, such as knowledge about the relation between theory and evidence (Kuhn, 2002), or about the procedural and conceptual basis for the design and interpretation of experiments (Chen & Klahr, 1999;Masnick & Klahr, 2003). Domain-specific knowledge includes facts and understanding about particular domains, such as physics, chemistry, or ecology.…”
Section: Instructional Materials: Physical or Virtual?mentioning
confidence: 99%
“…For example, Cells A and B were compared in a series of investigations by Klahr and colleagues (Chen & Klahr, 1999;Klahr & Nigam, 2004;Toth, Klahr, & Chen, 2000) using physical hands-on materials (physical ramps, springs, and sinking objects). The results of these studies demonstrated the relative effectiveness of direct instruction over discovery learning when teaching the ''control of variables strategy'' (CVS), a domain-general procedure for designing unconfounded experiments.…”
Section: Type Of Instruction: Direct or Discovery?mentioning
confidence: 99%
“…Some researchers think of science inquiry as domain-general reasoning or heuristics (e.g., Chen & Klahr, 1999;Klahr & Dunbar, 1988;Kuhn, 1989;Kuhn, Garcia-Mila, Zohar, & Andersen, 1995;Kuhn, Schauble, & Garcia-Mila, 1992;Zimmerman, 2000). This work centers on two key questions: (1) Can children control variables in controlled experiments?…”
Section: Different Views On Children's Abilities To Conduct Science Imentioning
confidence: 99%